Understanding the social emotional practices of therapists. Issue 1 (2nd January 2019) - Harvey, Shane T.; Marwick, Andreas; Baken, Don M.; Bimler, David; Dickson, Jan
Abstract: Emotions are central to the therapy process and skilful use by therapists of client emotion is an essential catalyst to client change. However, the contribution of emotion to the therapy process and how therapists' social emotional skills are incorporated into psychological practice is still unclear. Using a statistical method for mapping psychological constructs, therapists' social emotional skills were transformed into a "map" with three spatial dimensions, which was supported by comparative reliability checks. The nature of social emotional skills was further investigated by administering a Q-Sort of emotional practice items to 47 therapists. Ten highly applicable clusters of social emotional skills across seven style patterns with therapists were identified. Tentative links were drawn between demographic data and both clusters and therapist styles. These findings suggest therapists' social emotional skills can be organised into meaningful clusters and that therapists can be styled according to their responses across these clusters. Furthermore, gaps identified in the model suggest possible "blind spots" in the literature. The implications of these findings are significant for training and practice.